2022
DOI: 10.58567/jea01020001
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the connectedness and portfolio implications between Islamic and conventional bonds: Evidence from global and GCC regions

Abstract: We explore the connectedness and portfolio implications between Islamic and conventional bonds of global and GCC regions. We also compare which bonds are performing better during our sample period. Unlike previous studies, we focus on Islamic bond markets compared to their conventional counterparts and highlight the GCC bonds (Islamic and conventional) in respect of global bonds. We apply DCC-GJR-GARCH (1,1) method, Sharp ratio and portfolio implications strategy over the period from 01 September 2013 to 23 Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…China's financial system currently has apparent characteristics of transformation. The distribution of the financial system implies government guarantees, ownership discrimination, and weak risk appetite, which makes capital concentrated in the real estate industry (Ge, 2007;Amin et al, 2022). This is an important reason for the inefficient allocation of resources in the financial sector.…”
Section: Theoretical Mechanismmentioning
confidence: 99%
“…China's financial system currently has apparent characteristics of transformation. The distribution of the financial system implies government guarantees, ownership discrimination, and weak risk appetite, which makes capital concentrated in the real estate industry (Ge, 2007;Amin et al, 2022). This is an important reason for the inefficient allocation of resources in the financial sector.…”
Section: Theoretical Mechanismmentioning
confidence: 99%
“…In the case of investment in Islamic Sukuk such as Hajj Fund, having knowledge on such Sukuk, like knowing the procedures and benefits of the investment in these funds, seems to be crucial to making Muslim people more likely to invest in these Sukuk (Bin-Nashwan and Muneeza, 2021). Moreover, Amin et al (2022) revealed that knowledge plays a vital role in shaping individuals attitudes toward Islamic Sukuk. In addition, Karina and Pujiningsih (2023) argued that knowledge contributes to raising the level of investment in Islamic sukuk in Islamic countries worldwide.…”
Section: Literaturementioning
confidence: 99%
“…We add to the body of literature in two different ways. Initially, motivated by earlier research examining the Impact of behavioural finance factors on investment decisions (Abdeldayem and Aldulaimi, 2020a, 2020b; Almansour, 2017, 2020; Amin et al , 2022), we look at how the behavioural finance factors affect investment decisions of the Gulf Cooperation Council (GCC) cryptocurrency market. To extend most of these studies, we use a regime-switching model that accounts for two different market states.…”
Section: Introductionmentioning
confidence: 99%
“…We add to the body of literature in two different ways. Initially, motivated by earlier research examining the Impact of behavioural finance factors on investment decisions Aldulaimi, 2020a, 2020b;Almansour, 2017Almansour, , 2020Amin et al, 2022), we look at how the behavioural finance factors affect investment decisions of the Gulf IJOA 32,6…”
Section: Introductionmentioning
confidence: 99%